Role of some agrotechnical elements in the precision crop technology of cereals - Pepó, Péter (Acta Agraria Debreceniensis, 2012)
The crop models and precision technology have an important role in the development of winter wheat and maize agrotechnics, which crops have determinative role in Hungarian crop production. The effects of agrotechnical elements (crop rotation, fertilization, irrigation, crop protection, plant density) were studied in our longterm experiments on chernozem soil. Our scientific results proved that the high yields, and good yield stability were obtained in the input-intensive crop models. Maize had lower ecological adaptive capacity than winter wheat. The optimatization of agrotechnical elements reduces the harmful climatic effects so we can increase the yield and yield stability of cereals agro-ecosystems. The yields of wheat varied between 2 and 7 t ha-1 in extensive and 8 and 10 t ha-1 in intensive crop models and the yields of maize ranged between 2 and 11 t ha-1 and 10 and 15 t ha-1, respectively.